An in vitro CT Comparison of Gutta-Percha Removal with Two Rotary Systems and Hedstrom Files - Yadav, Pankaj; Bharath, Makonahalli Jaganath; Sahadev, Chickmagravalli Krishnegowda; Ramachandra, Praveen Kumar Makonahalli; Rao, Yogesh; Ali, Ambereen; Mohamed, Shahnawaz (Iranian Endodontic Journal, 2013)
Introduction: To evaluate the efficacy of NiTi mechanical rotary instrumentation and Hedstrom file for gutta-percha/sealer removal computed tomography (CT) was utilized in vitro. Materials and Methods: Thirty extracted human single rooted teeth, each with a single canal were selected. The samples were decoronated with a double faced diamond disk to have 17-mm root; teeth roots were instrumented with K-files up to master apical file #30 using step back technique. Samples were obturated using cold lateral condensation of gutta-percha and AH Plus root canal sealer. The teeth were then randomly divided into three groups of 10 specimens each. After 2 weeks 3-dimensional images of the roots were obtained by CT and the volume of root filling mass was measured. All the canals were then retreated by either the ProTaper retreatment files, Mtwo retreatment files or Hedstrom files. The canals were irrigated with 2 mL of 2.5% sodium hypochlorite irrigating solution during each change of instrument. The volume of remaining filling materials after the retreatment procedures was assessed by CT. Statistical analysis was performed with one-way ANOVA and Tukey’s post hoc test. Results: Neither of studied systems completely removed the root filling material. No significant difference was observed between the rotary systems. The volume of remaining filling materials was significantly less in rotary instrumentation than hand files. There was no significant difference for debris extruded from the apical foramen between the groups. Conclusion: Under the experimental conditions, Mtwo and ProTaper retreatment files left less gutta-percha and sealer than H files; however, complete removal of filling materials was not achieved by the three systems investigated.